Alzheimer’s disease and neuroinflammation: will new drugs in clinical trials pave the way to a multi-target therapy? - Melchiorri, Daniela; Merlo, Sara; Micallef, Benjamin; Borg, John-Joseph; Dráfi, František (Frontiers in Pharmacology, 2023)
Despite extensive research, no disease-modifying therapeutic option, able to prevent, cure or halt the progression of Alzheimer’s disease [AD], is currently available. AD, a devastating neurodegenerative pathology leading to dementia and death, is characterized by two pathological hallmarks, the extracellular deposits of amyloid beta (Aβ) and the intraneuronal deposits of neurofibrillary tangles (NFTs) consisting of altered hyperphosphorylated tau protein. Both have been widely studied and pharmacologically targeted for many years, without significant therapeutic results. In 2022, positive data on two monoclonal antibodies targeting Aβ, donanemab and lecanemab, followed by the 2023 FDA accelerated approval of lecanemab and the publication of the final results of the phase III Clarity AD study, have strengthened the hypothesis of a causal role of Aβ in the pathogenesis of AD. However, the magnitude of the clinical effect elicited by the two drugs is limited suggesting that additional pathological mechanisms may contribute to the disease. Cumulative studies have shown inflammation as one of the main contributors to the pathogenesis of AD, leading to the recognition of a specific role of neuroinflammation synergic with the Aβ and NFTs cascades. The present review provides an overview of the investigational drugs targeting neuroinflammation that are currently in clinical trials. Moreover, their mechanisms of action, their positioning in the pathological cascade of events that occur in the brain throughout AD disease and their potential benefit/limitation in the therapeutic strategy in AD are discussed and highlighted as well. In addition, the latest patent requests for inflammation-targeting therapeutics to be developed in AD will also be discussed.